Education System In Germany - Desi Ratna Sari Sari; Komarudin Sassi Sassi (Edumaspul: Jurnal Pendidikan, 2024)
Geographically, Germany is located in the middle of the European continent with an area of 356,957 square kilometers. Germany has a population of over 82 million people and about 8% of them are not German. Germany is one of the countries that has chosen to design a country based on educational design, because it is aware that a country's progress on all fronts is largely determined by the educational system from which it originates. Historically, education in Germany came from two sources, namely the church and the state. The formal education structure in Germany includes: primary education, lower secondary education and higher education depending on the state. Learning methods in Germany, starting from Kindergarten, have been designed in such a way, with careful planning.